Larvicidal, pupicidal and adult smoke toxic effects of Acanthospermum hispidum (DC) leaf crude extracts against mosquito vectors. (January 2018) - Vivekanandhan, Perumal; Senthil-Nathan, Sengottayan; Shivakumar, Muthugoundar Subramanian
Abstract: Plant based insecticides are now increasing being realized as a suitable for alternative to synthetic chemical insecticides. Acanthospermum hispidum leaf crude extract were tested for insecticidal potential against three major mosquitoes. A. hispidum leaves were extracted with different solvents such as hexane, petroleum benzene, chloroform, ethyl acetate, and acetone.Extracted crude metabolites were tested on larvae, pupa and adult mosquitoes belonging to An. Stephensi, Ae. aegypti, and Cx quinquefasciatus . Larval, pupal bioassay and smoke toxicity was done according to the WHO guidelines. The results, petroleum benzene crude extract have highest larvicidal, pupicidal activity with low LC50 and LC90 values for larval An.stephensi (20.965; 31.467) ppm; Ae. aegypti (15.223; 27.753) ppm; Cx. quinquefasciatus (29.095; 42.737) ppm and pupicidal LC50 and LC90 values were (41.234; 51.123); (32.168; 55.321); (39.213; 49.123) ppm respectively. Smoke toxicity test on adult mosquitoes, shows 69% in An.stephensi, 52% in Ae. Aegypti and 56% in Cx. quinquefasciatus . Our result clearly shows that A.hispidum leaf crude extract have a promising insecticidal activity against three mosquitoes. Highlights: A. hispidium is a weed of agricultural field. A. hispidium leaf extracts show promising mosquito larvicidal activity. A. hispidium coils are not effective in controlling adult mosquitoes.